Uso da terra e avaliação da naturalidade para o planejamento e manejo ambiental de bacias hidrográficas (Sudeste do Brasil) - Costa, Rômulo Theodoro (Universidade Federal de São Carlos, 2016)
Ecosystems managed manifest vulnerability according to decline of ecological resilience and depletion or loss of the main ecosystem service flows. Driving forces acting in landscape result in changes, which require regional management actions and / or local, in conjunction with other external factors. To operationalize these concepts in landscape management, this study approached the dynamics of the intensity changes in land use and conservation conditions of biodiversity scenarios, between 2004 and 2014, for the Jacaré-Guaçu and Jacaré-Pepira watershed rivers. The same analyzes were applied on floodplains formed at the Jacaré-Guaçu and Jacaré-Pepira headwaters in 2004, 2014 and 2015. Conditions of sustainability, involving environmental aspects from the land use and cover dynamic and sustainability indicators were assessed in these areas. Land use and cover dynamics maps were produced based on visual interpretation of Landsat images. Biodiversity conservation scenarios were designed based on Urbanity Index, which estimates the naturalness landscape conditions. The results showed a predominantly anthropogenic scenario, induced by expansion of the agricultural anthropogenic and non-agricultural anthropogenic land uses, and trough conversion of other land use types in sugarcane and forestry. The historical process of land use occupation for agricultural production remains the main driving force of landscape changes, which currently occupies more than 70% of the watersheds area. The Jacaré-Guaçu watershed river presented a critical scenery due to naturalness areas losses and critical naturalness areas increase. The biodiversity conservation scenery showed a reduction area and spatial displacement between 2004 and 2014, resulting from loss and fragmentation of natural capital in the watersheds. Despite the increase in natural vegetation areas, the watershed are far from a sustainable condition, according to loss of carrying capacity and the ecosystem services provision. There was no changes evidenced in land use and cover in floodplains, however, the localization of floodplains showed high vulnerability due to agricultural and urban areas, which indicates evidence of sustainability losses evidences.
Land use and naturalness assessment for watershed environmental planning and management (Southeastern Brazil).
Keywords: Capital natural; Indicadores estruturais da paisagem; Sustentabilidade; Serviços ecossistêmicos; Natura capital; Landscape structural indicator; Sustainability; Ecosystem services; CIENCIAS BIOLOGICAS::ECOLOGIA